1998
DOI: 10.1021/jp972465q
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Study of Jet-Cooled Complexes of Chiral Molecules:  The Role of Dispersive Forces in Chiral Discrimination

Abstract: Isomer formation in dimeric complexes of a chiral naphthalene derivative (2-naphthyl-1-ethanol) with nonchiral or chiral primary and secondary alcohols (n-propanol, 2-methyl-1-butanol, 2-butanol, 2-pentanol) has been studied by hole-burning spectroscopy. Besides the spectroscopic discrimination between the homochiral and heterochiral complexes, previously observed in the fluorescence excitation spectra, ground-state depletion experiments have shown that each diastereoisomer is cooled in the jet in several isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
1
8

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(148 citation statements)
references
References 29 publications
4
135
1
8
Order By: Relevance
“…6b and c). This result contrasts with the properties of a previously studied chiral naphthalene derivative, that bears similar substituents, and that has been shown to exist under a single isomeric form under supersonic-jet conditions [12]. These differences in behaviour may be related to a larger steric hindrance in the case of an anthracene ring.…”
Section: Bare Moleculecontrasting
confidence: 86%
“…6b and c). This result contrasts with the properties of a previously studied chiral naphthalene derivative, that bears similar substituents, and that has been shown to exist under a single isomeric form under supersonic-jet conditions [12]. These differences in behaviour may be related to a larger steric hindrance in the case of an anthracene ring.…”
Section: Bare Moleculecontrasting
confidence: 86%
“…[62,66] The LIF spectra of all complexes (see Figure 4) share common trends. The transition origin is always shifted down in energy relative to the isolated chromophore, indicating that the chromophore acts as the hydrogen-bond donor.…”
Section: -Naphthyl-1-ethanol Complexes With Secondary Alcoholsmentioning
confidence: 83%
“…The enantioselective shift of the electronic transition relative to the bare chromophore is a signature of chirality discrimination. It can be used to obtain information, though indirect, on the structure of the complexes, in particular on the role of the chromophore as a hydrogen-bond donor or acceptor, [62][63][64][65] the role of dispersion and conformation in the binding energy, [66] and the existence of OH···p interactions. [67][68][69][70] Besides providing mass-selective electronic spectra, REMPI experiments allow measuring the binding energy of the diastereomeric complexes.…”
Section: Spectroscopic Methodsmentioning
confidence: 99%
“…Gas-phase 2-butanol and 2-methylbutanoic acid can adopt several conformations as shown in Figure 4. 34 These are designated ga, ag, and gg (g ) gauche, a ) anti) and are illustrated for the (R)-enantiomer in Figure 4. Previous MP2 calculations have shown that, for 2-butanol, the ga conformation is ∼0.8 kcal/mol more stable than the ag conformer, which in turn is ∼1.2 kcal/mol more stable than the gg structure.…”
Section: Resultsmentioning
confidence: 99%